NEAR INFRARED IMAGING FOR SUBCUTANEOUS VEINS LOCALIZATION - SHAHZAD, AAMIR (2015)
The problem of peripheral dit11cult venous access (PDVA) occurs f()r the patients with different physiological characteristics during the intravenous (IV) catheterization process. Patients suffer with pain and trauma if they need more than one attempt tor proper catheter placement. In order to overcome the PDV A problem this research explores the near infrared (NIR) imaging modality for the localization of subcutaneous veins. There are few systems and devices available for veins localization but none of them until now is proven effective for all skin tone patients, wearable, easy to use and standardized. The overall goal of this work is to provide an effective solution to the PDV A problem using NIR imaging for veins localization during IV catheterization process.